2018
DOI: 10.1111/cid.12701
|View full text |Cite
|
Sign up to set email alerts
|

Buccal bone thickness at dental implants in the maxillary anterior region with large bony defects at time of immediate implant placement: A 1‐year cohort study

Abstract: Background There is lack of studies regarding preservation and possible changes in BBT at dental implants. Purpose To assess, on cone beam computer tomograms, the presence of bone at the time of tooth extraction in the maxillary esthetic region and the mean buccal bone thickness 1 month and 1 year after final restoration placement in patients with large bony defects. Material and Methods In a cohort study, patients were selected presenting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
4
25
2
Order By: Relevance
“…The three studied patients in this report presented with satisfying improvements as expressed in a PES score of 7.0 and patient questionnaire (VAS-scale score of 90.0). This is in line with other studies on immediate placement and provisionalization protocols, where PES scores of 7:5 ± 1:6 [22] and 6:8 ± 1:5 [23] were published on immediate implant placement protocols. All patients reached the threshold of clinical acceptability (score ≥ 6) [15].…”
supporting
confidence: 91%
“…The three studied patients in this report presented with satisfying improvements as expressed in a PES score of 7.0 and patient questionnaire (VAS-scale score of 90.0). This is in line with other studies on immediate placement and provisionalization protocols, where PES scores of 7:5 ± 1:6 [22] and 6:8 ± 1:5 [23] were published on immediate implant placement protocols. All patients reached the threshold of clinical acceptability (score ≥ 6) [15].…”
supporting
confidence: 91%
“…This suggestion is supported by the results of a recent cohort‐study, which showed that a new buccal bone wall can be created when grafting the implant‐socket gap buccal of the immediately placed implant. This wall buccal of the implant was well preserved for at least 1 year after immediate implant placement 29 . The created buccal bone wall even had a sufficient width in the test group, which showed more pronounced bone resorption than in the control group, to support the overlying peri‐implant soft tissues and to preserve the mid‐buccal mucosal level.…”
Section: Discussionmentioning
confidence: 94%
“…A small envelope flap was prepared at the mid‐buccal aspect, which disrupted the vascularization between the mucosa and periosteum. The disruption in the blood supply, together with the bone remodeling process after tooth extraction, 7,8 could have induced further loss of mid‐buccal bone 29,30 . Moreover, adding a CTG seems to have a larger effect on loss of BBT than the gingival phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…More details of the methods for measuring buccal bone thickness and the results of the one‐year follow‐up were described by Slagter, Raghoebar, et al (2015), Slagter et al (2017) and Meijer et al (2019).…”
Section: Methodsmentioning
confidence: 99%